THE ATTITUDE TOWARDS TREATMENT OF CARDIOVASCULAR DISEASES: A SURVEY OF PATIENTS OF STATE OUTPATIENT CLINICS AND PRIVATE MEDICAL CENTERS - O. N. Semenova; E. A. Naumova; Yu. G. Shvarts (Столичная издательская компания, 2015)
Aim. To study the differences in views on treatment among patients with cardiovascular diseases in state and private outpatient clinics, as well as the motivation for choosing one of these outpatient clinics.Material and methods. Anonymous and voluntary survey of cardiology patients (n=90) in 2 state (57.7%) and 3 private outpatient clinics (42.2%) was conducted in Saratov.Results. 33.3% of respondents were men; the median age was 65 years. Patients of state outpatient clinics were more likely to have retirement age (p=0.0008), low income (p=0.0006), history of hypertensive crises (p=0.0129) and chronic heart failure (p=0.0001). Patients of private outpatient clinics were more likely to have mental work (p=0.0001), higher education (p=0.0001), moderate income (p=0.0006). The difference in views on the disease and the attitude towards a doctor among patients of state and private clinics was shown.Conclusion. Patients of private outpatient clinics were more active, young, aimed at continuation of life. They are more likely to have higher education, mental work and moderate income. Patients of state outpatient clinics are "infatuated with their illness"; it is their "lifestyle". Paternalistic model of communication with doctors is expressed in all the patients.